Management of Cercospora Leaf Spot Disease of Mungbean (Vigna radiata) - , Rakesh Meena; , J K Babele; , Sitaram Seervi; , Rakesh Chaudhary; , Chandra Prakash Sharma (Archives of Current Research International, 2024)
This study aimed to investigate the effects of different fungicides on managing Cercospora leaf spot in Urdbean (Vigna radiata). The investigation was carried out at the experiment, Rainfed Organic Agriculture Research Farm Narayan Bagh, Institute of Agricultural Sciences, Department of Plant Pathology, Bundelkhand University, Jhansi (Utter Pradesh), during the Kharif season of 2023. The experiment was laid out in a randomized block design (RBD) with three replications. Fungicides were foliar applied after the initiation of the disease. Roko (thiophanate methyl) @ 0.05% (80.48%), followed by Kavach (Chlorothalonil) @ 0.01% (67.35%), Trichoderma harzianum @ 10 g/L (67.35%), Pseudomonas fluorescens @ 10 g/L (57.40%), Trichoderma + Pseudomonas @ 10 g/L (56.08%), M Guard 45 (Mancozeb) @ 0.2% (52.51%), Bavistin (Carbendazim) @ 0.10% (42.22%), Bavistin (Carbendazim) @ 0.05% (39.71%) and Control (67.35%). All the bioagents and fungicides tested against Cercospora leaf spot on per cent disease index and disease reduction in field conditions. The efficacy of bio-agents and fungicides as foliar spray were evaluated in field condition to find out the effectiveness of all treatments at 30 and 45 days of sowing.